Facial metrics as predictors of occlusal vertical dimension: an anthropometric analysis - Syed Muhammad Yadain; Soomro, Tufail Ahmed Soomro; Farooq Ahmed Abro; Mudaser Hussain Abbasi; Kamran Arzoo (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVES: Accurate reconstruction of facial features from skeletal remains, especially the maxillofacial region, is crucial in forensic identification. Specific facial measurements from anatomical landmarks provide important correlations with the vertical dimension of occlusion for forensic experts and dental procedures. There is a gap in such a study in Sargodha, therefore the study was planned to evaluate the correlation & association of facial measurements with the vertical dimension of occlusion (VDO) amongst the students of Rai Medical College, Sargodha. METHODOLOGY: The Observational Cross-sectional study engaged a cohort of 152 third-year MBBS students at Rai Medical College, Sargodha, comprising 74 males and 78 females. Institutional ethical approval was secured prior to the commencement of the research. Facial dimensions were meticulously evaluated, including the expanse from the corner of the eye to the angle of the mouth, the angle of the mouth to the tragus, and the Glabella to sub-nasion. The vertical dimension of occlusion (VDO) traverse from the base of the nose to the chin was precisely measured using a modified digital Vernier caliper. SPSS version 27 was used to analyze statistical data. RESULTS: One-sample t-tests confirmed that mean values for all variables were significantly different from zero. Significant correlations were observed between specific facial measurements but not with gender. CONCLUSION: This study concludes the facial morphology and demographic characteristics, revealing significant differences in facial measurements across demographic groups.